BRAND MANAGEMENT PRO-SOCIAL ACTIVITIES AS AN EFFECTIVE ELEMENT OF IMAGE STRATEGY - Nocoń, Marek; Różycka, Magdalena (Management and Administration Journal, 2022)
The aim of this article is to research the effectiveness of pro-social actions in the building of a brand image and if it really might be an effective determinant of marketing actions – which has an influence on consumer choices: chosen aspects of pro-social actions used in the strategies of NIVEA and Rossmann drugstores are explored here. In addition, analyzes of pro-social actions during pandemic was carried out. It is proved that companies which took a part in relief efforts during the crisis were appreciated by consumers; which helped when it came to creating brand value. The most important question seems to be not “Whether to invest in CSR?” but “How to invest?” This issue is sure to become the subject of numerous research projects and analyzes in the future.